Implementasi Augmented Reality sebagai Media Informasi Jadwal Penggunaan Ruang Laboratorium di Universitas Teknologi Yogyakarta - Arif Pramudwiatmoko; Ari Sugiharto; Ricky Armanda; Muhammad Fauzan Amana (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Universitas Teknologi Yogyakarta (UTY) operates several computer laboratory rooms used daily by students according to their scheduled times. Sometimes, these rooms experience sudden schedule changes, causing conflicts with other room bookings. This research aims to employ an Augmented Reality (AR)-based application for monitoring the dynamic schedule of lab room usage. The method utilizes a marker-based AR application, tested through black box implementation. The application successfully reads markers at distances of 10–90 cm, tilt angles of 10–80 degrees, and light intensities ranging from 40 to 250 lux. Under these conditions, the markers are readable, and the application responds by displaying virtual objects. Users of the lab rooms can utilize this AR application to identify changes in the scheduled usage plans at UTY as they occur.